Frequency of infection by Leptospira sp. in white neck squirrel (Sciurus stramineus) in a zoo of Lima city - Montes A., Daniel (2011)
The purpose of the study was to detect the frequency of antibodies against Leptospira sp in the wild neck white squirrel population (Sciurus stramineus) caught in the Parque de las Leyendas Zoo, Lima. Thirty five blood samples were collected from neck white squirrels, males and females of various ages that were trapped in various areas in the zoo. Samples were analyzed for antibodies against Leptospira sp by micro agglutination test. The 82.3% (29/35) of animals had antibodies against Leptospira sp of which 60% corresponded to the icterohemorraghiae serovar, followed by georgia (31.4%), canicola (5.7%), and australis (2.8%). None statistical difference between the presence of antibodies against Leptospira sp and the variables sex, age and area of trapping was found. The results indicated that leptospiral infection is present in the neck white squirrels, and the disease poses a health risk to animals and people working at the zoo.